(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Due to the Covid-19 outbreak and Movement Control Order (MCO), which was put in place to stop the potentially fatal outbreak, all higher education institutions across the country were forced to close. As a result, all the instruction, learning and assignment submission for students is done online. It might be difficult for students to submit their finished assignments to their lecturer, especially for those who live in rural areas and struggle with internet connectivity. Students may have to pay a high cost and drive to the city to obtain an internet connection. Images are the sole way to upload students; however, sometimes the pictures are too large, and sending them to the lecturer may take a day. Therefore, smart educational application for Engineering Science course was developed to provide high quality and effective learning and submitting lab work report to Polytechnic students. This application was created using the AppSheet platform's user-friendly features and can be used on a range of platforms, including phones, tablets, and web browsers. This application compiles all relevant learning materials, including videos of demonstrations, lab sheets, rubrics and others for students reports. Lecturers can get student reports in the form of spreadsheets, but they must autocrat spreadsheets to get student reports in the form of PDF files. There are 44 students from the Mechanical Engineering Department and Civil Engineering Department who are participating in this survey. This effectiveness study of a development DBS10012 Engineering Science Mobile application show that the content and interactive application is interesting, and the information provided is very helpful to students, the average overall mean score is 4.33 and 4.34 respectively. From this study, it was discovered that the goals for creating this application were successfully met. As a result, Students will be motivated to learn more in this course and submit their reports on time by this clever educational application.